Assessment of the influence of hypotherapy on psychosocial development of children until 18 years old - Woźniak, Patrycja; Weber-Nowakowska, Katarzyna (Journal of Education, Health and Sport, 2019)
Introduction. Hippotherapy is one of the most popular forms of zootherapy. The ability to provide a disabled person with a close contact with a horse has a strong impact on the emotional, cognitive, social and physical spheres. The aim of the study was to assess the impact of hippotherapy on psychosocial development of children up to the age of 18. Material and methods. The studied group consisted of children and adolescents aged 4-18. The study involved 100 people, and the studied group was divided into two groups: intellectually disabled (n=59) and physically disabled (n=41). Additionally, in order to study the effect of the length of therapy attendance in relation to the achieved effects, the studied group was divided into 3 subgroups depending on the duration of therapy attendance (T1-0-2 years, T2-3-4 years, T3-5-10 years). The research tool was an original questionnaire addressed to parents and carers of disabled children. Results. During the study a significant improvement in the motor sphere was achieved, it was mainly an improvement of balance, posture and muscular strength. In the psychic sphere, aspects such as communication skills, speech development, motivation and family life improved. Conclusion: Hippotherapy has a positive effect on the psychosocial development of children, taking into account both the motoric and mental spheres.